Tagging in 3DXChat animated sex game porn production - Caetano, Mayara Araujo (Informa UK Limited, 2025)
This qualitative study of tagging practices within online animated pornographic content produced inside the massive online multiplayer game 3DXChat examines how user-generated porn producers position themselves within the structure of the online free porn platform XVideos and the porn conventions they relate their videos to. Based on a purposeful sample of 112 videos uploaded to XVideos, I retrieved 166 unique tags. I contextualize them through a two-year online ethnography experience and discuss them according to information categorization (taxonomy and folksonomy), sexual data within online porn platforms, and pornography. I conclude that 3DXChat user-generated porn is subject to the consolidated sex-tech structures of its time, leaning towards conventional porn categories; the few social tags reflect the in-between stage of ‘niched-mainstream’. Tags exemplify the serialization, indexation, influences, and potential limitations for sexual play.